Reformulation of Article 412 Law Number 1 of 2023on Cohabitation from a Legal Certainty Perspective - Imera Azzahra Alivia; Prija Djatmika; Nurini Aprilianda (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2026)
The criminalization of cohabitation under Article 412 paragraphs (1) and (2) of Law Number 1 of 2023 on the National Criminal Code raises significant juridical concerns, particularly with regard to legal certainty and proportionality. This study focuses on examining the juridical implications arising from the formulation of Article 412 and on proposing an ideal regulatory framework for the criminal offense of cohabitation in Indonesia in the future. Employing a normative juridical research method with statutory and conceptual approaches, this research analyzes the consequences of ambiguous legal formulations, especially the vague elements of “living together as husband and wife outside marriage,” the complaint-based nature of the offense, and the unclear limitation of eligible complainants. The findings indicate that these weaknesses undermine the principle of lex certa, create risks of multiple interpretations, and potentially lead to selective criminalization and violations of legal certainty. Furthermore, the study argues that such deficiencies place Article 412 within the category of a voidable norm that may be subject to constitutional review. Accordingly, this research proposes a reformulation of Article 412 by clarifying and operationalizing the elements of the offense, restricting the scope of complaint-based prosecution, and explicitly defining the age limits of child complainants, in order to ensure legal certainty, proportionality, and the protection of human rights.